10+18=28
17+11=28
OR
2x=28 where x=14
4x where x=7
Answer:
what do you need help wth ?
Step-by-step explanation:
Answer:
<h2>
</h2>
Step-by-step explanation:
g(x) = x² - 2x - 6
h(x) = 2x² - 5x + 2
To find (h-g) (-2) we must first find h - g(x)
To find h - g(x) subtract g(x) from h(x)
We have
<h3>
</h3><h3>
</h3>
To find (h-g) (-2) substitute the value of x that's - 2 into (h - g)(x) that's replace every x in (h - g)(x) by - 2
That's
<h3>
</h3>
We have the final answer as
<h3>
</h3>
Hope this helps you
Answer:5n+6
Step-by-step explanation :an=a1+d(n-1)
=1+(-5)(n-1) or 1+-5n+5
an=-5n+6